Efectos De Un Programa De Actividades Motrices Para La Praxia Global En El Grupo De Jardín Del Icbf De Circasia Quindío (2016)
The research “effects of a program of motor activities, for the global praxia in the ICBF kinder garden group from Circasia Quindio” has as a reference the theory by Vitor da Fonseca. The research was developed under the quasi-experimental quantity methodology, and a pretest-postest design, the global praxia was assumed as a study variable, with children amount 4 and 5 years old; where two groups were studied, one of them was called control group (it did not receive intervention) and the other was called the experimental group (it was submitted to a program of motor activities). The information was analyzed in a statistic processing where the variable was put into the base of an Excel 2010 data; in which values were assigned to each of the variables in order to analyze the global praxia. Subsequently it was made the statistic processing in the SPSS v.20 software, once the supposed statistics were proved, the interpersonal and intrapersonal differences were analyzed with Wilcoxon y U. of mann-whitney, for the comparison of the inter group variables. The generated results showed meaningful statistics differences in four of the five proposed facts in the intervened group (experimental group), with a lower score in the dysmetry component. Unlike, the control group did not get any change in the facts evaluated for the global praxia.